General Ordinances of the City of Aspen, §§ 293, ASPEN DAILY TIMES, Jul. 27, 1886, at 3-6 (Aspen, Colorado). - (:unkn) unknown (General Publisher, 1886)
No gun, weapon or explosive shall be used in any shooting gallery, of a size to endanger life or limb, or to frighten horses, or to cause any annoyance to the people of the vicinity in which such gallery is situated, and all such galleries shall be securely enclosed and have protection and planking, or other obstructions sufficient to arrest any projectile in and about such galleries..."
--
Keywords: SHOOTING RANGES OR GALLERIES